Somatic Embryogenesis as Key Technology for Shaping the Rubber Tree of the Future - Mignon, Eline; Werbrouck, Stefaan (Frontiers in Plant Science, 2018)
Worldwide, Hevea producers face the need to replant large surfaces in the coming years. The rubber yield per ha, produced by trees grafted on heterogeneous illegitimate seedling rootstocks, has reached its maximum. For long-standing Hevea clones, as for a lot of other tree species, one of the consequences of physiological aging is reduced in vitro growth and the lack of a proper geotropic (tap)root system. Somatic embryogenesis on young inner seed integument or stamen filaments provides a mean to regain ontogenetic juvenility. The process is limited by irregular germination of the somatic embryos. Nevertheless, with the obtained in vitro plants, juvenile lines have been established of the most important profitable rubber tree clones. Currently they are micropropagated on a commercial scale. Moreover, the produced plants can serve as mother plants for propagation by means of macro-cutting. Somatic embryogenesis enables the production of transgenic Hevea brasiliensis as well. Genes conferring plant disease resistance, abiotic stress tolerance and production of foreign proteins in the lactiferous vessels will further shape the rubber tree of the future.